2011
DOI: 10.1002/dev.20602
|View full text |Cite
|
Sign up to set email alerts
|

Daily stress increases risky decision‐making in adolescents: A preliminary study

Abstract: Adolescence is characterized as a developmental period of risky decision-making. During this developmental window there is also a marked increase in actual and perceived stress. Acute stress increases risky decision-making in adults, but no research has examined this phenomenon in adolescents. In this study, an ecologically relevant approach was used to document daily self-reports of stress in adolescents and an emerging adult comparison group. Participants visited the laboratory twice: once each when they end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 45 publications
2
40
1
1
Order By: Relevance
“…Notably, no effects of moderating factors such as sex, age, neuroendocrine response, and stress-to-task latency were observed. This is surprising given growing research supporting the importance of such moderators, for example stress-related risk-taking increases in adolescents [77; 78]. Though it is premature to draw strong conclusions given small sample size, likely without adequate representation of moderating factors and great methodological variability across included studies (e.g., uncertainty level), the meta-analysis represents an important step forward and helps shape impending research.…”
Section: Stress and Risk-takingmentioning
confidence: 99%
“…Notably, no effects of moderating factors such as sex, age, neuroendocrine response, and stress-to-task latency were observed. This is surprising given growing research supporting the importance of such moderators, for example stress-related risk-taking increases in adolescents [77; 78]. Though it is premature to draw strong conclusions given small sample size, likely without adequate representation of moderating factors and great methodological variability across included studies (e.g., uncertainty level), the meta-analysis represents an important step forward and helps shape impending research.…”
Section: Stress and Risk-takingmentioning
confidence: 99%
“…There was a negative association between ventral striatum response and maternal warmth, suggesting at a minimum that the ventral striatum may respond quite differently to stressors that are experienced during the adolescent period. Galván and McGlennen (2012) used a daily diary approach to monitor and compare 14–17 year-old adolescents’ daily stress to that of 18–21 year-old emerging adults. Results indicated that adolescent participants made more risky decisions during high stress relative to low stress, suggesting that stress impacts behavior in a similar, albeit more exaggerated, manner in adolescents relative to adults (Galván & McGlennen, 2012).…”
Section: Development Of Ventral Striatal Dopaminergic Motivational Symentioning
confidence: 99%
“…In the current study, we utilized a well‐validated risk‐taking task (Galván & McGlennen, ) in which participants' choices between certain and uncertain (i.e., risky) outcomes were associated with specific probabilities of monetary outcomes. We implemented a novel manipulation, in which adolescents completed the task twice: once during which their decisions impacted only themselves (monetary gains and losses), and the other during which their decisions impacted only their parent's outcomes.…”
Section: Introductionmentioning
confidence: 99%